Bahasa dan Konteks di TikTok: Analisis Deiksis dalam Komentar Warganet pada Video Erika Richardo - Maipa, Sitti; Mustari, Nabila; Dwi Cahyani, Reny; Candra Dewi, Anita (AIJER: Algazali International Journal Of Educational Research, 2025)
Abstrack: This study aims to identify and analyze the use of deixis in the comments on TikTok videos uploaded by content creator Erika Richardo. Employing a descriptive qualitative method and a pragmatic approach, this research categorizes comment data into five types of deixis: personal, spatial, temporal, discourse, and social. The results indicate that netizens use various types of deixis to construct interactions, convey information, express emotions, and build social relationships in the digital context. The use of personal deixis helps users identify themselves and others, spatial and temporal deixis provide situational context, discourse deixis refers to elements within the conversation, and social deixis reflects norms and social relationships among users. This research provides insights into how language is dynamically used in social media to create meaning and strengthen interactions between users.